P111 Reaching out – gum in the general practice setting. (8th June 2017) - Watt, Joanne; Streeter, Thomas; Ashton, Susan; Battersby, Cara; Herbert, Sophie
Abstract : Introduction: Providing accessible GU services in rural areas is difficult. Providing a service in General Practice (GP), close to patients' homes may increase access (particularly to those who might not otherwise test) and avoid the perceived stigma of attending a GUM clinic. A GUM service was set up in 2008 within a general practice setting (syndromic management), in an area of high need (HIV prevalence 2.58 PHE 2015).We aim to describe the outcomes of running a GU clinic within GP. Methods: Demographic, attendance and diagnoses data was collected and analysed from 2008–2016. Results: A total of 1081 patients were seen (1826 attendances) with a median of 200(186–221) per year. 604 diagnoses of infection were made (33.1%). 922(85%) lived in the town where the clinic was held. 53.8%(582) had never been seen in GU in our county before compared with 32.6% in the hubs. 440 (41%) were men of which 40(9%) were MSM. Mean age for attendees was 29 (28 at the main GU hub). Total number <20 year olds fell from 2007-2016 but those aged 21–35yrs and 45–60yrs increased. Table 1 shows the distribution of GUMCAD diagnoses. There were 426 DNAs (18.9%), 42% were follow-ups. Overall HIV testing was refused in 15.5% cases, (30% in 2007 but 7% in 2016). Discussion: In rural areas where transport links are limited, a GU clinic run in GP offers an efficient, anonymous service. Services can be offered in this setting with few extra resources providing an alternative point of access for patients.